Structural Optimisation of a Suspension Control Arm Using a Bi-Evolutionary Bone Remodelling Inspired Algorithm and the Radial Point Interpolation Method - Carlos Oliveira; Ana Pais; Jorge Belinha (Applied Sciences)
Today, topological structural optimisation is a valuable computational technique for designing mechanical components with optimal mass-to-stiffness ratios. Thus, this work aims to assess the performance of the Radial Point Interpolation Method (RPIM) when compared with the well-established Finite Element Method (FEM) within the context of a vehicle suspension control arm’s structural optimisation process. Additionally, another objective of this work is to propose an optimised design for the suspension control arm. Being a meshless method, RPIM allows one to discretise the problem’s domain with an unstructured nodal distribution. Since RPIM relies on a weak form equation to establish the system of equations, it is necessary to additionally discretise the problem domain with a set of background integration points. Then, using the influence domain concept, nodal connectivity is established for each integration point. RPIM shape functions are constructed using polynomial and radial basis functions with interpolating properties. The RPIM linear elastic formulation is then coupled with a bi-evolutionary bone remodelling algorithm, allowing for non-linear structural optimisation analyses and achieving solutions with optimal stiffness/mass ratios. In this work, a vehicle suspension control arm is analysed. The obtained solutions were evaluated, revealing that RPIM allows better solutions with enhanced truss connections and a higher number of intermediate densities. Assuming the obtained optimised solutions, four models are investigated, incorporating established design principles for material removal commonly used in vehicle suspension control arms. The proposed models showed a significant mass reduction, between 18.3% and 31.5%, without losing their stiffness in the same amount. It was found that the models presented a stiffness reduction between 5.4% and 9.8%. The obtained results show that RPIM is capable of delivering solutions similar to FEM, confirming it as an alternative numerical technique.